Click, Shop, Smile: How Service Convenience Shapes E-Retail Customer Satisfaction - Br Ginting , Nita; Nasution, Muhammad Dharma Tuah Putra (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
In the rapidly evolving world of e-commerce, service convenience has become a key factor influencing customer satisfaction. This study aims to analyze the impact of service convenience dimensions on customer satisfaction in e-retailing services. The examined dimensions include access convenience, search convenience, evaluation convenience, ordering convenience, logistics convenience, and reverse logistics convenience. We collected data using a quantitative approach by distributing a questionnaire to 111 users of the Shopee e-commerce platform. The regression analysis results indicate that all dimensions of service convenience have a positive and significant effect on customer satisfaction, with logistics convenience being the most dominant factor. The managerial implications of this study highlight the need for e-retailers to improve logistics systems, simplify the ordering process, and provide better accessibility to enhance customer experience and loyalty.